2016
DOI: 10.18632/oncotarget.13629
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the VEGF-C/VEGFR3 axis suppresses Slug-mediated cancer metastasis and stemness via inhibition of KRAS/YAP1 signaling

Abstract: Vascular endothelial growth factor-C (VEGF-C) has been implicated in epithelial-mesenchymal transition (EMT) processes and various human cancers, including skin cancer. Skin cancer is an aggressive human malignancy with increasing incidence worldwide; however, the underlying mechanisms involved in VEGF-C-induced skin cancer stemness and metastasis remain unclear. Here, we report that VEGF-C enhances skin cancer migration, invasion and stemness through Slug up-regulation. Oncomine database analysis indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 67 publications
2
42
0
Order By: Relevance
“…However, we and others did not detect VEGF receptors on the different RCC cell lines 56. VEGFC signaling in RCC depends on the VEGFR3 co-receptor neuropilin 2 57, and this autocrine loop probably maintains stemness as already described in skin cancers, and consequently, a low ability to proliferate 58. α 9 β 1 integrin was described as a VEGFC receptor mediating the migration of breast cancer cells 59, 60.…”
Section: Discussionmentioning
confidence: 47%
“…However, we and others did not detect VEGF receptors on the different RCC cell lines 56. VEGFC signaling in RCC depends on the VEGFR3 co-receptor neuropilin 2 57, and this autocrine loop probably maintains stemness as already described in skin cancers, and consequently, a low ability to proliferate 58. α 9 β 1 integrin was described as a VEGFC receptor mediating the migration of breast cancer cells 59, 60.…”
Section: Discussionmentioning
confidence: 47%
“…LAMA1, an extracellular glycoprotein of the laminin family, is an essential component of basement membranes, being involved in tumorigenesis and other biological processes [ 17 ]. VEGFC results in the promotion of angiogenesis and/or lymphangiogenesis [ 18 ]. Moreover, it has been reported that FLT4 significantly correlate with the different stages of cervical carcinogenesis [ 19 ]; the ligand of FLT4 might effecting tumor cells directly to affect cancer development and progression [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study revealed that the vascular endothelial growth factor receptor (VEGFR) signaling pathway plays a major role in angiogenesis (20) and that KRAS plays a key role in VEGF signaling (21). To ascertain these results, we knocked down KRAS using shRNA and determined the expression level of VEGFA in HCT116 cells.…”
Section: Kras Is a Key Regulator In Vegf-related Angiogenesismentioning
confidence: 98%